Análise da viabilidade técnico-econômica da geração de energia solar fotovoltaica em unidades de confinamento bovino com sombreamento artificial - MORAES, Emerson Ricardo de (Universidade Federal do Pará, 2020)
The increase in worldwide population caused a rising search by food, both origins, vegetable and animal. Due the decrease in rural areas to destined for livestock activities, as a result to greater use of areas for agriculture, there are an intensification in cattle farming, the aim to use a smallest area of property for a large quantities of animals, at same time, associated the animal welfare and its thermal comfort, and provide improvement in production system. This population increase also implicate in higher demand for electric energy sources, due to the improvement of living standards and advances technologic. The objective this work was to analyze the technical and economic viability of the generation of solar photovoltaic energy, in line the livestock activity, using the shading sheds coverage in beef cattle feedlot. A bibliographic study was carried out on the animal yield of the Nellore breed, in confinement in a tropical climate, in the situation of total exposure to the sun or with the use of shady sheds. Three scenarios were created for the analysis of animal welfare, the animal being confined in the open, confinement with the use of shading sheds and confinement with the generation of solar photovoltaic energy on the roof of its shading shed. Two alternative meteorological stations were made to collected the samples of local climatic variables, and calculate the indices of thermal comfort and animal well-being, and to identify the possible beef cattle yield at the study site. Budgets for items and services were made for the execution of projects for containment pens, roof sheds and distributed generation of photovoltaic solar energy, for further analysis of the technical and economic feasibility of the projects. The results showed greater economic viability, with greater profitability and shorter return on investment, for the treatments of confinement pens in the open, which present, for the population of 200, 600 and 1000 animals, an IRR of 75.86%, 86.71% and 89.88%, PI of 4.68, 5.34 and 5.53 and discounted payback of 1.49, 1.29 and 1.24 years, respectively, while for the construction of the entire structure together with the generation of solar photovoltaic energy, it was obtained, in the same order, IRR of 22.30%, 14.09% and 14.62%, PI of 1.58, 1.18 and 1.21 and discounted payback of 5.17, 7.71 and 7.48 years. Although the economic feasibility was not the best, treatments with a photovoltaic energy generation system connected to the distribution network, when built together with the structures of confinement and shed pens, provide greater comfort to the animals and enable the generation of energy renewable. The result of the photovoltaic installation was more economically viable, when mounted on shed structures already existing in confinement systems for 200 animals, which presented an IRR of 23.72%, PI of 1.65 and a discounted payback of 4.88 years. It is concluded that the most viable design option for the creation of animals in feedlot, is the open model for the largest number of animals, while for the generation of energy, it is the system connected to the low voltage network mounted on shed structures already in feedlot systems for 200 animals, without the need for demand contracts, containing 200 photovoltaic panels.